2020
DOI: 10.1080/09540121.2020.1785997
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure prophylaxis among men who have sex with men in Côte d’Ivoire: a quantitative study of acceptability

Abstract: This cross sectional study was conducted in 2018 in Côte d'Ivoire to assess PrEP acceptability among men who have sex with men (MSM). Two hundred and one men were asked on their intention to use PrEP if made available. Logistic regression accounting for the sampling design was used to analyze associations between high PrEP acceptability and different independent variables including barriers and facilitators. Participants were mostly young (mean age = 25 years), educated (82% with secondary/postsecondary educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The results of our study reveal that PrEP awareness had already increased over the course of the study, likely via participants of the parallel CohMSM-PrEP study ( 24 ). This finding corroborates quantitative studies, indicating that oral PrEP awareness in these communities may already have increased ( 36 , 37 ). Stimulating peer communication and supporting PrEP users in actively disclosing their PrEP status to other community members can be important strategies for increasing its uptake ( 38 ).…”
Section: Discussionsupporting
confidence: 89%
“…The results of our study reveal that PrEP awareness had already increased over the course of the study, likely via participants of the parallel CohMSM-PrEP study ( 24 ). This finding corroborates quantitative studies, indicating that oral PrEP awareness in these communities may already have increased ( 36 , 37 ). Stimulating peer communication and supporting PrEP users in actively disclosing their PrEP status to other community members can be important strategies for increasing its uptake ( 38 ).…”
Section: Discussionsupporting
confidence: 89%
“…Interventions based on demandside described findings including communication, education and information and peerbased interventions on outcome of HIV are unsatisfactory as they rarely reduce prevalence or incidence of HIV. Few studies and trials showed in reviews assessed interventions for increasing circumcision and pre exposure prophylaxis demand, though data from these components are still in emerging stage [110][111][112][113][114][115][116]. Additional research is needed for understating the reason of decreased uptake for these approaches and assessments needed for improved interventions to increase the adherence and uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Availability was quoted as a state where PrEP can be accessible by MSM at any given time (Diabaté et al, 2021) and to know where to get it (Kota et al, 2021). The availability of PrEP can be affected by many issues, such…”
Section: Theme 2-prep Availability and Accessibilitymentioning
confidence: 99%
“…Literature has identified that a majority of MSM do not take PrEP due to fear of unforeseen side effects of PrEP, which might be long-term (Gredig et al, 2016). The cost The availability of PrEP facilitates willingness to use it (Ahouada et al, 2020;Frankis et al, 2016) Availability of PrEP influences its uptake (Ahouada et al, 2020;Chakrapani et al, 2015;Dean et al, 2023;Diabaté et al, 2021;Galea et al, 2011;Kimani et al, 2022;Pelletier et al, 2019) Preference for PrEP to be accessible at MSM networks (Ahouada et al, 2020;Graham et al, 2023;Harawa et al, 2016;Pelletier et al, 2019) Accessibility of IEC material on PrEP increases knowledge and awareness of PrEP (Graham et al, 2023) Inaccessibility to PrEP influences low uptake (Adeagbo et al, 2021;Han et al, 2019;Harawa et al,…”
Section: Screeningmentioning
confidence: 99%
See 1 more Smart Citation